2007
DOI: 10.1053/j.gastro.2007.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte-Dependent and Th2 Cytokine-Associated Colitis in Mice Deficient in Wiskott-Aldrich Syndrome Protein

Abstract: Background & Aims: Controversy exists as to whether patients with inflammatory bowel disease have an underlying immunodeficiency. We have focused on a murine model of the Wiskott-Aldrich syndrome, an immunodeficiency in which autoimmunity can manifest in the form of an inflammatory bowel disease-like illness. Wiskott-Aldrich syndrome protein (WASP) deficiency in mice results in similar clinical features. We characterized the colitis in WASP-deficient mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 44 publications
4
77
2
Order By: Relevance
“…Such effect would be consistent with the correction of WASp expression in T cells and the normalization of their T-helper and regulatory functions, because TH2 cells and regulatory T cells have a major function in the development and control of the autoimmune colitis in this model. 20,23 The correction of colitis provides an important preclinical validation for the WAS LV and confirms the effects that we had previously reported with an LV expressing the WAS transgene under control of the PGK promoter. 16 Although the WAS gene promoter is weaker than the PGK promoter, it generates equivalent levels of protein WASp in transduced cells, as reported previously.…”
Section: Discussionsupporting
confidence: 83%
“…Such effect would be consistent with the correction of WASp expression in T cells and the normalization of their T-helper and regulatory functions, because TH2 cells and regulatory T cells have a major function in the development and control of the autoimmune colitis in this model. 20,23 The correction of colitis provides an important preclinical validation for the WAS LV and confirms the effects that we had previously reported with an LV expressing the WAS transgene under control of the PGK promoter. 16 Although the WAS gene promoter is weaker than the PGK promoter, it generates equivalent levels of protein WASp in transduced cells, as reported previously.…”
Section: Discussionsupporting
confidence: 83%
“…It is possible that, in the absence of N-WASP, the production of cytokines and/or their receptors may be altered. In support of this hypothesis, studies from our laboratory have demonstrated that colonic lamina propria T cells from WASP-deficient animals produce elevated levels of IL-4, a cytokine known to induce keratinocyte proliferation (47). Surprisingly, we have found that epidermal differentiation and wound healing, processes that are associated with marked cytoskeletal changes, are not affected by the absence of N-WASP.…”
Section: N-wasp Regulates Keratinocyte Proliferation But Is Not Requmentioning
confidence: 61%
“…In contrast, mast cells loaded with serum from nonfood-sensitized animals were not activated by either food extract, which further demonstrated that IgE-dependent degranulation was antigen specific and established that screening of antibody IgG1 was observed (Supplemental Figure 1D). The observation that food-specific IgE could be detected in Was -/-mice on 3 different genetic backgrounds indicated that sensitization to ingested antigens did not result from colonic inflammation since, in contrast to Was -/-mice on the colitis-prone 129SvEv background (26,27), animals on the BALB/c and C57BL/6 background are resistant to colitis (Supplemental Figure 1, E and F).…”
Section: Sensitization To Food Antigens and Food Allergy Are Enrichedmentioning
confidence: 99%